An Anaplastic Lymphoma Kinase Immunohistochemistry–Negative but Fluorescence In Situ Hybridization–Positive Lung Adenocarcinoma Is Resistant to Crizotinib. Issue 12 (December 2016) - Shi, Ruoshi; Varella‐Garcia, Marileila; Li, Ming; Ludkovski, Olga; Danesh, Arnavaz; Ng, Christine; Pham, Nhu‐An; Pugh, Trevor; Shepherd, Frances A.; Tsao, Ming‐Sound
ABSTRACT : Introduction: : Oncogenic fusion of anaplastic lymphoma kinase (ALK) with echinoderm microtubule associated protein like 4 protein or other partner genes occurs in 3% to 6% of lung adenocarcinomas. Although fluorescence in situ hybridization (FISH) is the accepted standard for detecting anaplastic lymphoma receptor tyrosine kinase gene ( ALK ) gene rearrangement that gives rise to new fusion genes, not all ALK FISH–positive patients respond to ALK inhibitor therapies. We report here an ALK FISH–positive patient‐derived xenograft (PDX) that was nonresponsive to crizotinib therapy. Methods: : The PDX patient human lung cancer (PHLC402) was established in NOD/SCID mice from a patient with resected pT4N1M0 lung adenocarcinoma. ALK gene status was investigated using the standard FISH break‐apart assay, reverse‐transcriptase quantitative polymerase chain reaction, RNA sequencing and immunohistochemical assay using the 5A4 antibody. PHLC402 was treated with crizotinib (50 mg/kg) by daily oral gavage. Results: : ALK FISH assay was positive in both the primary patient tumor and PDX, which were negative for ALK protein expression by immunohistochemical analysis. ALK fusion product was not detected by RNA sequencing and reverse‐transcriptase quantitative polymerase chain reaction comparing the 5′ and 3′ ALK transcript levels. Crizotinib treatment of PHLC402 grown in mice resulted in no tumor response. Conclusion: : ALK protein expression may be necessary for ALK FISH–positive lung cancer to be responsive to ALK inhibitor therapy.